YAP regulates cell mechanics by controlling focal adhesion assembly - Nardone, Giorgia; Oliver-De La Cruz, Jorge; Vrbsky, Jan; Martini, Cecilia; Pribyl, Jan; Skládal, Petr; Pešl, Martin; Caluori, Guido; Pagliari, Stefania; Martino, Fabiana; Maceckova, Zuzana; Hajduch, Marian; et al. (Nature communications, 2017)
Hippo effectors YAP/TAZ act as on-off mechanosensing switches by sensing modifications in extracellular matrix (ECM) composition and mechanics. The regulation of their activity has been described by a hierarchical model in which elements of Hippo pathway are under the control of focal adhesions (FAs). Here we unveil the molecular mechanism by which cell spreading and RhoA GTPase activity control FA formation through YAP to stabilize the anchorage of the actin cytoskeleton to the cell membrane. This mechanism requires YAP co-transcriptional function and involves the activation of genes encoding for integrins and FA docking proteins. Tuning YAP transcriptional activity leads to the modification of cell mechanics, force development and adhesion strength, and determines cell shape, migration and differentiation. These results provide new insights into the mechanism of YAP mechanosensing activity and qualify this Hippo effector as the key determinant of cell mechanics in response to ECM cues.
Keywords: extracelulární matrix; mikrofilamenta; Cell Cycle Proteins; buněčné linie; lidé; buněčný převod mechanických signálů; Cell Membrane; rhoA protein vázající GTP; Gene Expression Profiling; stanovení celkové genové exprese; Cell Line, Tumor; Cell Line; Actin Cytoskeleton; proteiny buněčného cyklu; Transcription Factors; Humans; Mechanotransduction, Cellular; rhoA GTP-Binding Protein; buněčná diferenciace; transkripční faktory; tvar buňky; Cell Shape; HEK293 buňky; Cell Movement; jaderné proteiny; buněčná membrána; pohyb buněk; Focal Adhesions; Extracellular Matrix; nádorové buněčné linie; Cell Differentiation; fokální adheze; HEK293 Cells; Nuclear Proteins